Fracture Nonunion of the Clavicle After Surgical Reduction in a 13-Year-Old Girl: A Case Report. Issue 4 (October 2021) - Davat, Marie; Steiger, Christina N.; Tabard-Fougere, Anne; Dayer, Romain; Ceroni, Dimitri
Abstract : Case: Although congenital nonunion of the clavicle is a well-known pathology in children, posttraumatic nonunion is a rare entity. Nonunion after open reduction and internal fixation of a clavicle fracture is exceptional in the pediatric population. We report on a patient presenting posttraumatic pseudarthrosis of the clavicle after surgical treatment. Pseudarthrosis was resected, and the defect was bridged with an iliac crest autograft, supplemented with bone morphogenetic protein, and fixed with an elastic stable intramedullary nail. Conclusion: This procedure offered enough stability for achieving fracture consolidation and is a safe alternative to plating in clavicle nonunion.